Transcriptomic analysis of disease resistance responses using a tobacco-Botrytis cinerea pathosystem - Basson, Carin Elizabeth (Stellenbosch : Stellenbosch University, 2017)
Thesis (PhDAgric)--Stellenbosch University, 2017.